2009
DOI: 10.1088/0004-637x/705/2/l104
|View full text |Cite
|
Sign up to set email alerts
|

The Star Formation Rate in the Reionization Era as Indicated by Gamma-Ray Bursts

Abstract: High-redshift gamma-ray bursts (GRBs) offer an extraordinary opportunity to study aspects of the early Universe, including the cosmic star formation rate (SFR). Motivated by the two recent highest-z GRBs, GRB 080913 at z ≃ 6.7 and GRB 090423 at z ≃ 8.1, and more than four years of Swift observations, we first confirm that the GRB rate does not trace the SFR in an unbiased way. Correcting for this, we find that the implied SFR to beyond z = 8 is consistent with LBG-based measurements after accounting for unseen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

39
385
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 300 publications
(428 citation statements)
references
References 46 publications
39
385
4
Order By: Relevance
“…Some examples of CSFR measurements which differ substantially from the trend shown by the data collected by MD14 can be found in, e.g., Faucher-Giguére et al (2008) and Kistler et al (2009).…”
Section: Csfr: Cosmic Star Formation Ratementioning
confidence: 86%
“…Some examples of CSFR measurements which differ substantially from the trend shown by the data collected by MD14 can be found in, e.g., Faucher-Giguére et al (2008) and Kistler et al (2009).…”
Section: Csfr: Cosmic Star Formation Ratementioning
confidence: 86%
“…The first results obtained on host galaxy samples showed that they were primarily blue with lowmass, and low-metallicity (e.g., Fruchter et al 1999;Le Floc'h et al 2003;Berger et al 2003;Christensen, Hjorth & Gorosabel 2004;Tanvir et al 2004;Savaglio, Glazebrook & Le Borgne 2009) and suggested that the metallicity of the host could be a proxy for the progenitor. Such proxies exerted a strict metallicity-cut (e.g., Langer & Norman 2006;Salvaterra & Chincarini 2007;Butler, Bloom & Poznanski 2010;Elliott et al 2012), such that only host galaxies below a given value could host a LGRB, which lead to predictions that the CSFH flattens at higher redshifts (e.g., Kistler et al 2009;Salvaterra et al 2012). However, these host galaxy studies were optically biased, which when accounted for, systematically more massive galaxies were found (e.g., Krühler et al 2011;Rossi et al 2012).…”
Section: Manymentioning
confidence: 99%
“…1. We compare it to several values obtained from the literature, de- termined from star-forming galaxies (Mannucci et al 2007;Bouwens et al 2008;Li 2008), Lyman-break galaxies (Laporte et al 2012;Zheng et al 2012), Lyman-α emitters (Ota et al 2008), and LGRBs (Kistler et al 2009;Ishida, de Souza & Ferrara 2011) that reach a redshift of z ∼ 10. Both the CSFH of the FiBY simulation and the measured distribution are seen to be consistent throughout redshift.…”
Section: Cosmic Star Formation Historymentioning
confidence: 99%
“…Evolution with z of the Star Formation Efficiency (SFE) defined by the ratio between far-infrared luminosity and molecular gas mass (LFIR /M(H2 )), for the sources detected between 0.2 < z < 0.6 (black full dots, and upward-arrows), compared with other detections in the literature (cf Combes et al 2010). The red curve is a schematic line summarizing the cosmic star formation history, from the compilation by Hopkins & Beacom (2006), implemented with the GRB data by Kistler et al (2009), and the optical data from Bouwens et al (2008).…”
Section: F Combesmentioning
confidence: 99%